A general purpose array with a broad spectrum of applications - Schneider, Hans Jürgen; Händler, Wolfgang; Hofmann, Fridolin (Informatik-Fachberichte - Computer Architecture, Workshop of the Gesellschaft für Informatik, 1976)
UnivIS-Import:2015-04-16:Pub.1976.tech.IMMD.IMMD2.agener

Architecture and realization of the modular expandable multiprocessor system MEMSY - Sieh, Volkmar; Pataricza, Andras; Turowski, Stefan; Thiel, Thomas; Dal Cin, Mario; Hohl, Wolfgang; Dalibor, Stefan; Eckert, Törless; Grygier, Andreas; Hessenauer, Hellmut; Hildebrand, Uwe; Honig, Joachim; et al. (1st International Conference on Massively Parallel Computing Systems: The Challenges of General-Purpose and Special-Purpose Computing, MPCS 1994, 1994)
Keywords: Fault Tolerance; Scalability; MIMD; Multiprocessor

Performance analysis of parallel programs based on model calculations - Hofmann, Fridolin; Bolch, Gunter; et al. (1994)
Modeling parallel programs can help the developer during the design phase of a particular implementation on the one hand and on the other hand provide principle insights which are needed to establish design principles for the development of parallel programs. It is important that the model used provides a sufficient but not too detailed representation of the parallel program. Precedence graphs provide an easy to understand representation of the structure of parallel programs. Information about the behavior of parallel programs during execution can be obtained by assigning distributions of the execution times of the subtasks to the nodes of these graphs. In this paper we introduce truncated θ-exponential polynomials as a class of distributions suitable for the modeling of task run-times of massively parallel programs. As opposed to classical exponential polynomials known from literature, truncated θ-exponential polynomials allow the representation of distributions with finite domain and are therefore appropriate for the analysis of massively parallel systems. We present approximation formulas which allow the approximate calculation of the total execution time for large models in particular. We provide formulas for the parallel execution of a large number of subtasks. We also give a method to estimate the total execution time of regular graphs, which are also very important in the field of modeling parallel programs. © 1994.
UnivIS-Import:2016-06-23:Pub.1994.tech.IMMD.IMMD4.perfor_5
Keywords: Dynamic scheduler; Exponential polynomial; Extreme value distribution; Massively parallel system; Modeling; Parallel computing; Performance analysis; Precedence graph; Regular structure; Static scheduler